Liber Ordinarius z Ołoboku znany także jako Horae diurnae, Officium parvum z Mogiły. Próba wyjaśnienia proweniencji kodeksu - Wałkówski, Andrzej; Wolnik, Franciszek (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The subject of research is the origin of law-liturgical code containing detailed provisions on the exercise of liturgy of the hours, mass and other celebrations in the liturgical year. Code was written down at the turn of the thirteenth and fourteenth centuries. This kind of book in the Middle Ages was defined as Liber ordinarius. However, if you study the scientific literature manuscript like this was determined as the Horae diurnae (Officium parvum). Also, literature and catalogs show that it comes from the library of the Cistercian monastery at Mogiła, where Czartoryski Library purchased it in 1875 for 10 zloty. The examined code contains the ownership note indicating that in 1367 it was found in the Cistercian monastery in Ołobok. There is no indication that it came from the Mogiła. Besides the above-mentioned note there is no other information concerning the place of creation or retention of the Code. The research was carried out with three provenance tracks. The first was an analysis of the liturgy, the second was based on paleographic research, and the third is an attempt to re-create on the basis of the Ołobok monastery’s history and Czartoryski Library’s collection of manuscripts the probable circumstances of changes in ownership of the tested code. Liturgical analysis indicated that the manuscript was created in the Silesian Cistercian environment, probably in a monastery in Lubiąż. Researches of the code indicate that the manuscript has a graphic features commonly found in Lubiąż at the turn of the thirteenth and fourteenth centuries. Recreating the history of the Abbey in Ołobok as well as Czartoryski Library’s manuscripts the history of the Code was outlined.